Impact of COVID-19 on Construction Projects: The Case of India - A. Rani, Hafnidar; Abdelrahman, M. Farouk; Anandh, K. S.; Almutairi, Saud; Rahimi, A. Rahman (MDPI, 2022)
The COVID-19 pandemic has affected the whole world, including India, especially in the construction sector. The study aims to identify, compare, and analyze the critical pandemic impacts (CPI) on construction projects in India. To achieve this, 40 interviews with industry professionals, are followed by a systematic review to identify the CPI. The data collected was used to develop a survey, sent to industry professionals all over India, with a return of 92 valid responses. The data were analyzed using reliability analysis, mean score ranking, overlap analysis, agreement analysis, and correlation analysis. The overall critical pandemic impact includes ‘labor scarcity,’ ‘supply chain disruption,’ ‘decreased construction productivity,’ ‘increased project financing rejection rate,’ and ‘reduced foreign investment in the construction industry.’ The findings could aid authorities and policymakers in taking suitable actions toward solving the current CPI in India. Project managers and owners could consider the current CPI in order to formulate better plans. Overcoming CPI could lead to an economic leap in India.